Simulation Software as a Calculation Tool for Traffic Capacity Assessment - Cernicky, Lubomir; Kalasova, Alica; Mikulski, Jerzy (Communications - Scientific letters of the University of Zilina, 2016)
Every town faces many problems one of which is ensuring good traffic situation in its territory. Road network in towns is limited by density of existing buildings and every traffic increase can lead to road network overcrowding. Therefore towns have to plan the future traffic in the way the roads are prevented from occurring traffic problems. In order to prevent traffic problems within the city every larger investment plan which may have impact on traffic has to come under the traffic capacity assessment before is approved by city. This paper is focused on various tools that may be used in traffic capacity assessment of every greater investment plan. You can find comparison of Aimsun simulation outputs, OmniTrans simulation outputs, and outputs of analytical calculation according to technical regulations valid in Slovakia in this paper.